Nutrição mineral e produção de óleo essencial em plantações de corymbia citriodora fertilizado com composto orgânico de lodo de esgoto - Piazon Neto, Mario [UNESP] (2012)
The sewage sludge is becoming an increasingly big problem for cities, with the population growing; there is an increased proportion of this material. An alternative for disposal this waste is the use in agriculture and forestry, with a special ability of the latter, since the end product is not intended for human or animal feeding. Based on this, is to find out if the treated sewage sludge (biosolids) has the ability to supply adequate nutrition for the cultivation of Corymbia citriodora (Hook.), a species of multiple uses, which highlights the essential oil extraction.This study aims to compare the fertilizing forests homogeneous species Corymbia citriodora for the production of essential oil with biosolids (2.5, 5.0, 10 and 20 ton / ha K), usual chemical fertilizer, only one treatment with potassium and an absolute control without any fertilization. Before the experiment be deployed under field conditions, there will be a soil test recommendations as a basis for mineral fertilizers. Several parameters will be evaluated every three months during one year, which will be the following: height, crown diameter, level of chlorophyll in leaves and leaf analysis and every six months will be done soil and leaf analysis. At the time of leaves collect, dry weight will be measured in addition to the oil yield and quality, quantifying the content of citronelal by the method of chromatography. There were statistical differences for height, crown diameter and index of green, and for crown diameter indicated differences from the first evaluation (after three months). For nutrition, chemical analysis of leaves was ...